Assessment of the repeatability of column experiments results on the example of a conservative tracer - Pietrzak, Damian; Kania, Jarosław; Kmiecik, Ewa; Baba, Alper (Geologos, 2025)
Most studies on the behavior of pollutants in the groundwater environment are carried out in laboratories, and the results are then implemented at local and regional levels using model simulations or analytical solutions. Column experiments are used to determine the transport characteristics of inorganic and organic chemicals in the soil and water environment. Although column experiments have been conducted regularly for many years, there is currently no established standard protocol for setting up and conducting them to ensure consistent results. The repeatability of column experiments was evaluated for soils, which differ primarily in the silt and clay content, using a conservative tracer susceptible only to advection and dispersion processes to reduce the number of variables affecting the results of the study which arise in a case of using reactive contaminants. The column experiments performed according to the adopted methodology are characterized by high repeatability of the obtained test results for the transport parameters, regardless of the type of injection or the chosen column length (only a small-scale effect is visible). Based on the results, it can be noticed that for the same soil the values of the pore–water velocity for different types of injections and column lengths are very similar. The percentage difference between the values of pore–water velocity obtained for both tested soils does not exceed 5% and for individual pairs of parallel column experiments it does not exceed 3%.